International Symposium on Microjoining, Cambridge, UK, 20-21 September 1988 - International Symposium on Microjoining (1988 : Cambridge, UK); Jones, S. B.; Welding Institute (Great Britain) (Cambridge, Eng; : Welding Institute, 1989)
22